2018
DOI: 10.1021/acs.iecr.7b04103
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Nucleation and Fabricating Nanoparticulate Formulation of Sorafenib Using a High-Gravity Rotating Packed Bed

Abstract: Nucleation is the initial step of the crystallization process and is the significant step to prepare nanometer-sized crystalline materials. In this work, we systematically investigated the nucleation kinetics of poorly water-soluble drug sorafenib when precipitated by liquid antisolvent precipitation in high-gravity rotating packed bed. We found that high-gravity field tremendously promoted the nucleation rate, and the nucleation rate was increased by 2–3 orders of magnitude over that in the stirred tank react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…However, when continuing to increase the AS/S FRR from 20 to 30, large flaky drug particles began to appear. This was in agreement with the result reported in our previous work [ 22 ].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…However, when continuing to increase the AS/S FRR from 20 to 30, large flaky drug particles began to appear. This was in agreement with the result reported in our previous work [ 22 ].…”
Section: Resultssupporting
confidence: 94%
“…The growth rate of the crystal is inhibited at a high nucleation rate, which promotes the assembly of nanoparticles with a narrow size distribution. The nucleation kinetics of poorly water-soluble drug during the HGAP process were investigated in our previous study [ 22 ]. We found that excipients, high-gravity field and AS/S flow ratio were key factors in influencing nucleation rate, and hence affected particle size [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sorafenib (SFN) is an endorsed drug to treat hepatocellular carcinoma (HCC) [1]. SFN is a multi-kinase inhibitor that prolongs overall survival and postpones the opportunity to progression in patients with advanced HCC who are not candidates for remedial treatment [2]. SFN is a weakly basic drug with a higher absorption rate under acidic conditions in the stomach than in the intestine [3].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Therefore, an RPB with a small volume can achieve higher volumetric mass transfer coefficients. 6 Many researchers have proved the advantage of RPBs in absorption, 7,8 desorption, 9 distillation, 10,11 crystallization, 12 production of nanoparticles, 13,14 etc. In addition, there are many successful industrial applications of RPBs.…”
Section: Introductionmentioning
confidence: 99%